2011
DOI: 10.1371/journal.pone.0025003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Single-Dose and Triple-Dose Albendazole and Mebendazole against Soil-Transmitted Helminths and Taenia spp.: A Randomized Controlled Trial

Abstract: BackgroundThe control of soil-transmitted helminth (STH) infections currently relies on the large-scale administration of single-dose oral albendazole or mebendazole. However, these treatment regimens have limited efficacy against hookworm and Trichuris trichiura in terms of cure rates (CR), whereas fecal egg reduction rates (ERR) are generally high for all common STH species. We compared the efficacy of single-dose versus triple-dose treatment against hookworm and other STHs in a community-based randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
145
5
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 37 publications
(54 reference statements)
15
145
5
2
Order By: Relevance
“…China. However, they are comparable to reports by Steinmann and co-workers 34 from other Bulang communities characterized by similar socio-ecological contexts where multiple species helminth infection was also common. 11,[20][21][22] Taken together, these data emphasize that, although P.R.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…China. However, they are comparable to reports by Steinmann and co-workers 34 from other Bulang communities characterized by similar socio-ecological contexts where multiple species helminth infection was also common. 11,[20][21][22] Taken together, these data emphasize that, although P.R.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the cure rate of only 19.6% for T. trichiura as observed in our trial is much lower than that reported from a previous trial with triple-dose albendazole treatment in the same area (56%). 34 It is difficult to explain these observations because sampling and diagnostic efforts were comparable and the same field team was involved in both trials. It should be noted, however that from a public health point of view, the egg reduction rate rather than the cure rate should be considered when determining anthelmintic drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports are available from Cameroon, Ethiopia, and Tanzania, with cure rates ranging from 93 to 99% and from 69 to 93% (33)(34)(35), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Yunnan, observed a CR of 96.7%, 91.5%, and 19.6% for hookworm, A. lumbricoides, and T. trichiura, respectively; while Steinmann et al (2011) 17 in single-dose versus triple dose treatment trial against hookworm and other STHs in a community based randomized controlled trial in the People's Republic of China, observed albendazole cured significantly more hookworm infections than mebendazole in both treatment regimens (single-dose: respective CRs e 69% (55e81%) and 29% (20e45%); triple dose: respective CRs 92% (81e98%) and 54% (46e71%)). The above studies suggest that the CRs obtained with single-oral dose of ALB & MBZ against STH and other nematodes seldom achieve complete cure.…”
mentioning
confidence: 95%